2012
DOI: 10.1029/2011jc007760
|View full text |Cite
|
Sign up to set email alerts
|

Air‐sea interface in hurricane conditions

Abstract: [1] Improving hurricane prediction models requires better understanding of complex processes taking place at the air-sea interface at high wind speeds. The change of the air-sea interaction regime in hurricane conditions has been linked to the mechanism of direct disruption of the air-sea interface by pressure fluctuations working against the surface tension force. This can be achieved through the Kelvin-Helmholtz type instability. In order to investigate this mechanism, we have conducted a series of 3D numeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Laboratory22 and numerical27 experiments, conducted with monochromatic waves, unexpectedly demonstrated that KH instability of the air-water interface does take place, though predominantly near wave crests. The local conditions near the wave crest are more favorable for KH instability development because the instantaneous interfacial shear near wave crests is higher than the time-averaged shear.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory22 and numerical27 experiments, conducted with monochromatic waves, unexpectedly demonstrated that KH instability of the air-water interface does take place, though predominantly near wave crests. The local conditions near the wave crest are more favorable for KH instability development because the instantaneous interfacial shear near wave crests is higher than the time-averaged shear.…”
Section: Resultsmentioning
confidence: 99%
“…The VOF 3D LES model27 included realistic sea surface tension and was forced with wind stress corresponding to U 10 ≈ 40 ms -1 . The images are taken with a shadow-imager in a small air-sea interaction tank at ASIST at wind speed corresponding to U 10 ≈ 40 ms −1 as well.…”
Section: Figurementioning
confidence: 99%
“…Figure shows the results of a numerical experiment performed with the multiphase volume of fluid large eddy simulation (VOF LES) computational fluid dynamics model described in Soloviev et al (). A very fine mesh with the spatial resolution at the air‐water interface Δx×Δy×Δz=0.75×0.75×0.75 mm 3 was used in this work (versus 5.0×5.0×1.0 mm 3 in Soloviev et al, ). The surface tension coefficient at the air‐water interface was set at 0.072 N m −1 ; periodic boundary conditions were set along the x axis; and slippery boundary conditions at the bottom and side walls.…”
Section: The State Of the Air‐sea Interface Under Tropical Cyclonesmentioning
confidence: 99%
“…The environmental extremes have been gaining significant attention over recent years, and this topic is well reflected in the current special issue. Papers by Soloviev et al [2012], Liu et al [2012], Holthuijsen et al [2012]are dedicated to air‐sea interface and boundary layer in the hurricane‐like conditions. Specifically, Liu et al [2012]suggested a new parameterization for wind stress which takes into account the spray effects in the boundary layer and is able to describe the sea drag across all weather conditions, from low‐ to hurricane‐like winds and agrees with the available observations Holthuijsen et al [2012]…”
Section: Discussionmentioning
confidence: 99%